Buildings Energy Certification System in Portugal: Ten years later - Petra Vaquero (Energy Reports, 2020)
Buildings Energy Certification~System (SCE) was implemented in Portugal through the publication of the Decree-Law 78/2006 and due to the adjustment of national legislation imposed by EPBD 2002. Thus, since January 1, 2009 all residential and service buildings, new, refurbished or existing must have an Energy Certificate in any construction, purchase or lease process. During the last 10 years, and not only due to EPBD recast that occur in 2010, the legislation has undergone dozens of changes, interpretations and corrections being important to realize their impact on the main indicators of buildings energy efficiency. Through the application of the three calculation methodologies, adopted by SCE in these 10 years, to a single-family house that was certified in 2009, it was possible to verify that the main indicators of energy efficiency have changed drastically.
Keywords: 330; Energy efficiency; Buildings regulation; Energy certification; EPBD; SCE